Ironia, mejoza i hiperbola - Schrott, Raoul; Jakobs, Arthur (Poznańskie Studia Polonistyczne. Seria Literacka, 2019)
The subject of the translated article is irony understood as one of the formative elements of human speech. The author discusses the etymology of this idea, referring primarily to its definition formulated by Socrates, showing its relations with sarcasm, cynicism, meiosis and hyperbole. In terms of content, irony also has a moral element, since it is a challenge to traditional ideas, beliefs or shared cultural references. Irony is also a stylistic convention of poetics, helping to portray in literature what is paradoxical and ambiguous.